Raziskovanje spolnega vedenja v Sloveniji - Švab, Alenka (Družboslovne razprave, 2010)
The article analyses the history of research on sexual behaviour in Slovenia with an emphasis on three aspects: the content of the research, the way it was carried out, and what was the research tradition in comparison with Western countries. The authors find that in comparison with Western countries there is a lack of tradition. The research started at the beginning of the 1990s. Previously there was some research on contraceptive and reproductive behaviour although no questions on sexual behaviour were included. The majority of surveys come from the field of public health, yet the surveys do not differ in organisational and methodological aspects or in the sorts of questions they included. The only difference is that social science surveys included more questions on the positive aspects of sexual behaviour (sexual satisfaction), while the public health survey focused on negative aspects (risky sexual behaviour).
Keywords: Sexual behavior; Spolno vedenje; Družboslovno raziskovanje; Social science research; Javno zdravje; Public health; Slovenia; Slovenija; sexual intercourse; spolnost; javno zdravstvo; spolno prenosljive bolezni